Advancements and challenges in UAV-based communication networks: A comprehensive scholarly analysis - Fayu Wan; Muhammad Bilal Yaseen; Muhammad Bilal Riaz; Anum Shafiq; Atul Thakur; Md Owahedur Rahman (Results in Engineering)
This scholarly paper provides a comprehensive examination of UAV-based communication networks, focusing on challenges, innovations, and future directions. Drawing from a synthesis of eighty research articles published in top-tier IEEE journals from 2014 to 2024, the study elaborates on the specific challenges and limitations associated with UAV-based communication networks mentioned in the literature. The methodology involves a systematic literature review, thematic analysis, and synthesis of key findings. The review analysis highlights significant challenges, including limited endurance, spectrum allocation, regulatory constraints, and integration issues. Moreover, it underscores the effectiveness of UAV-based communication networks in disaster response, agriculture, surveillance, and security through real-world case studies. Additionally, the paper explores the potential of machine learning techniques and game theory in optimizing user connectivity and enhancing network performance. The implications of this research are profound, suggesting the need for continued research and innovation to address current challenges, enhance network performance, and explore new applications. Interdisciplinary collaboration, regulatory cooperation, and technological advancements are vital for realizing the full potential of UAV-based communication networks and shaping the future of connectivity. This scholarly analysis contributes to the academic discourse on UAV-based communication networks, guiding researchers, industry stakeholders, and policymakers in navigating the complex landscape and fostering innovation in this transformative field.